PASKAH SEBAGAI PUNCAK PEWAHYUAAN ALLAH TRITUNGGAL - Juandi, Juandi; Firmanto, Antonius Denny; Aluwesia, Nanik (STIPAS Keuskupan Agung Kupang, 2021)
God Trinity is a concept that is always used as an endless discussion material. The Trinity concept in the Old Testament is explained implicitly while in the New Testament, the concept of God Trinity gets explicit explanations. Easter events marked by miserable, died and peak is the resurrection of Jesus, it is proof and sign of God's love to humans. Evidence of God's love to humans is marked by the events of the Maria containing the Holy Spirit, and fulfilled in Easter events. The presence of Jesus World is to restore human relations with God that has been damaged by human sin. In Easter, human sins are abolished and the relationship with God has been restored. That is the peak of God's love for humans. In this paper it will be presented as a reasons for Easter to become a saving and peak faith in the revelation of the Trinity of God to humans. Thus, after an estimated event, there is no other revelation of the other Trinity to humans. To support this paper, the author looks for various literacy and supporting church documents. In the end, as new people who have been redeemed should be able to become individuals who proclaim about the atonement to all humans